An investigation of the effects of nasogastric tubes on the young, normal swallowing mechanism - Clarkson, Phillipa Sarah (Division of Communication Sciences and Disorders, 2018)
The aim of the present study was to objectively address the effects of nasogastric.tubes on normal swallowing physiology. In addition, the differential effects of fine and wide-bore nasogastric tubes on swallowing function, were targeted for investigation. Only young, normal subjects were studied, to eliminate age-related swallowing changes (Robbins et al., 1992). The method of videofluoroscopy was used to determine the relationship between different size nasogastric tubes on the temporal parameters of normal oropharyngeal swallowing movements and bolus transit motion. Each subject served as their own control, allowing comparison of the individual's normal swallowing patterns with their swallowing in the presence of a nasogastric tube.